Kajian Potensi Energi Bayu sebagai Penggerak Pompa Pengairan Pertanian Daerah Sare Aceh Besar - Meliagrina Meliagrina; Ahmad Syuhada; Zahrul Fuadi (Jurnal Teknik Mesin Unsyiah, 2016)
The amount of agricultural lands has been converted into residential land and industrial land since a lot of farmland in the mountains has been opened. Groundwater and river has been used to irrigate the agricultural lands. Farmers in the mountainous areas typically use his physical effort to get water from river to agricultural land. This causes inefficiency of working for farmers thus the agricultural productivity is not optimal. Owing the fact that agricultural land is far from the electricity resources (PLN) therefore a small capital farmer must use pump to irrigate their agricultural lands. Hence, farmers have to spend big amount of money to buy fuel to drive the agricultural pump engine. Thus, it is necessary to have a specific research on the availability of wind energy in order to mobilize the agricultural pump engine in the mountainous area. In this case, the authors have calculated and analyzed the potential of wind energy to drive the pump in the village of Sare, Aceh Besar. From the analysis it has been obtained that the average wind speed of 6,41 m/s with the diameter of rotor turbine about 3 meter result in 1005,26 watt of wind turbine power. This power can be used to power a 20 m head static pump, requiring 650 watt to provide irrigation for 19 hectare of agricultural land 7 hrs/day. HOMER and Epanet 2.2 software are used to conduct simulation for power system generation. The result of HOMER simulation shows the lowest NPC value of US$ 10.028 with the cost of energy (CoE) of USD 0.717 kWh. The system could produce electricity power in a year of 3.452 kWh and the working length of the generating power system is 15 years